Investigating tributyltin's toxic effects: Intestinal barrier and neuroenteric disruption in rat's jejunum - Oliveira, I. C.C.S. [UNESP]; Marinsek, G. P. [UNESP]; Gonçalves, A. R.N. [UNESP]; Lopes, B. S. [UNESP]; Correia, L. V.B.; Da Silva, R. C.B.; Castro, I. B.; Mari, R. B. [UNESP] (Elsevier, 2024)
The expansion of economic activities in coastal areas has significantly increased chemical contamination, leading to major environmental challenges. Contaminants enter the human body through the food chain, particularly via seafood and water consumption, triggering biomagnification and bioaccumulation processes. The gastrointestinal tract (GIT) acts as a selective barrier, protecting against chemical pollutants and maintaining homeostasis through a complex network of cells and immune responses. This study assessed impact of tributyltin (TBT), a highly toxic organometallic compound used in antifouling coatings for ships, on the GIT and myenteric neural plasticity in young rats. TBT exposure leads to histopathological changes, including epithelial detachment and inflammatory foci, especially at lower environmental doses. The study found that TBT causes significant reductions in villi height, increases in goblet cells and intraepithelial lymphocytes, and disrupts the myenteric plexus, with higher densities of extraganglionic neurons in exposed animals.
Keywords: Antifouling; Extraganglionic neurons; Gut defense; Morphophysiology